Computational aerodynamic studies of the MIBC “Moscow-City” complex during sequential construction of buildings - S. G. Saiyan; A. M. Efimova (Vestnik MGSU)
Introduction. Computational studies of aerodynamic interference of the MIBC “Moscow-City” complex with sequential construction of buildings, taking into account their chronological order are carried out. Previous studies only considered the designed buildings and structures, along with the surrounding actual and future development, without computational analysis of their impact on the already constructed buildings. The study demonstrates the importance of considering aerodynamic interference in numerical simulation. It draws conclusions on the mutual influence of high-rise buildings and identifies the wind attack angles that contribute to the maximum values of the average and pulsation components of the wind action.Materials and methods. Numerical simulation methods in the ANSYS Fluent software package were used to conduct computational analysis. Quasi-two-dimensional aerodynamic models of the building complex of MIBC “Moscow-City” were developed, verified and validated for the computational studies.Results. The paper presents the results of 256 design cases, including 13 design variants for the consecutive erection of buildings in the MIBC “Moscow-City” complex and 19 calculations of freestanding high-rise buildings. Each calculation was performed for eight wind attack directions. The paper provides the average and pulsation total aerodynamic forces and moments for each building of the complex, depending on the chronology of building construction. The radar charts of aerodynamic coefficients (average and pulsation) were used to determine the most dangerous wind directions. The number of constructed buildings in the MIBC “Moscow-City” complex was taken into account.Conclusions. Based on the example of the sequential construction of the MIBC “Moscow-City” complex, this study emphasizes the importance of considering aerodynamic interference in dense and changing urban environments for both new and existing buildings. Aerodynamic interference can result in both wind shielding effects and increased wind, which affects the mechanical safety of buildings and structures.